Every Child Matters and children’s spiritual rights: does the new holistic approach to children’s care address children’s spiritual well‐being? - Watson, Jacqueline (International journal of children's spirituality, 2006)
Every Child Matters is a major change programme aimed at integrating all services for children and young people in England. It seeks to enable a new holistic approach to their care and so improve a number of outcomes for children, thus improving their overall well‐being. Every Child Matters seeks to address the rights of the child to improved life chances but also their right to a voice in decisions made about their care. Although Every Child Matters seeks to improve a number of outcomes for children, it makes no mention of their spiritual well‐being. This article examines Every Child Matters’ holistic approach and discusses in some detail its attempt to put into practice the right of children and young people to have their voices listened to and their opinions valued. The article points to the absence of any specific reference to children’s spirituality in Every Child Matters, and asks whether its holistic approach and its recognition of children’s right to be heard are sufficient to address children’s and young people’s spiritual rights, particularly in education.